Study of metallothionein oxidation by using of chip CE - Krizkova, Sona; Adam, Vojtech; Kizek, Rene (Electrophoresis, 2009)
Metallothionein (MT) is a low-molecular mass protein playing an essential role in homeostasis of heavy metals ions. We used a chip-based CE for quantitative study of MT oxidation. After oxidation of MT by H(2)O(2) we observed marked decrease in peaks heights and shift of peaks positions to higher molecular mass, which corresponded with the time of the oxidation. Moreover, we observed that the proportion of high-molecular forms of MT was markedly increased. The oxidative changes were successfully reversed by using of reducing agent prior to electrophoresis. Our method can reveal the stability MT aggregates, of which biological role still remains unclear.
Keywords: elektroforéza kapilární; mikrofluidní analytické techniky; polymery; oxidace-redukce; Microfluidic Analytical Techniques; Oxidation-Reduction; analýza rozptylu; Sensitivity and Specificity; senzitivita a specificita; Polymers; Analysis of Variance; metalothionein; peroxid vodíku; Hydrogen Peroxide; Metallothionein; Electrophoresis, Capillary